Implementation of artificial intelligence for brand equity - Yuhan Dong (Cogent Business & Management)
This article endeavors to answer the following research question: What is the impact of Artificial Intelligence (AI) on branding and the trends, pros, and pitfalls? 519 AI-branding related research articles from 1988 till early 2024 are collected from Scopus online database to build the dataset for bibliometric analysis with dimensions of co-occurrence, citation and co-citation in titles and abstracts. The author innovatively forged a framework to combine quantitative bibliometric method and qualitative model of Consumer Based Brand Equity (CBBE) x Data/Technology to explore the dynamics and the trends. Based on the distribution of articles in different years, the author divides the time period into 3 phases from 1988 to 2024, finding a quick doubling time of 1.61 years of AI-branding literature. Future development trends in AI-Branding subsume cross-disciplinary application, greater presence of AI applications in the areas of learning, communication and perception of AI Core II domain. Anthropomorphism, lack of explains ability and transparency concerns are rising, as well as new challenges to keep balance between short-term performance and long-term brand equity. As branding entering the AI era, both researchers and practitioners will benefit from this research for the timely update and holistic depiction.